1996
DOI: 10.1002/(sici)1096-9861(19960311)366:3<478::aid-cne8>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior commissure of the wallaby (Macropus eugenii): Adult morphology and development

Abstract: In metatheria, all neo- and paleo-cortical commissural connections are made by the anterior commissure. We have examined the adult morphology of this commissure and its development in a diprotodontid metatherian, the wallaby (Macropus eugenii), at both the light and electron microscope level. The total number of axons in the adult anterior commissure was 21.7 million, of which 55-62% were myelinated. The dorsal two thirds of the commissure, containing neocortical commissural axons, showed a higher percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…According to the dual-process framework of metacognition, metacognition has two processes: metacognitive feelings, which are mainly based on nonanalytic processes, and metacognitive judgments, which are based on analytic processes [ 46 ]. Additional ERP studies on insight have also suggested that the P170 component may be automatic and occur without much conscious processing at an early stage of information processing [ [47] , [48] , [49] ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the dual-process framework of metacognition, metacognition has two processes: metacognitive feelings, which are mainly based on nonanalytic processes, and metacognitive judgments, which are based on analytic processes [ 46 ]. Additional ERP studies on insight have also suggested that the P170 component may be automatic and occur without much conscious processing at an early stage of information processing [ [47] , [48] , [49] ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, axon numbers in the anterior commissure of the tammar wallaby do not peak until around 150 days and only 4% are myelinated by 216 days compared with around 60% in the adult. 57 In contrast, myelination of axons of the corpus callosum in rat pups begins between 10 and 13 days after birth and achieves its maximum rate by about one month after birth. 58 All of the above conclusions are conditional on there being few confounding effects of halothane anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…This process became more sophisticated during the evolution of mammals. In marsupials (infraclass Marsupialia) and monotremes (order Monotremata), interhemispheric communication is carried out through an evolutionary old structure, the anterior commissure ( Flower, 1865 ; Smith, 1897 , 1902 , 1937 ; Abbie, 1939 ; Ashwell et al, 1996 ; Johnston, 2004 ; Suárez et al, 2014b ). During the evolution of placental mammals (infraclass Eutheria), a new structure appeared—the corpus callosum (Latin corpus callosum, CC).…”
Section: Introductionmentioning
confidence: 99%